2021
DOI: 10.1029/2020pa004037
|View full text |Cite
|
Sign up to set email alerts
|

The Miocene: The Future of the Past

Abstract: The Miocene epoch (23.03-5.33 Ma) was a time interval of global warmth, relative to today.Continental configurations and mountain topography transitioned toward modern conditions, and many flora and fauna evolved into the same taxa that exist today. Miocene climate was dynamic: long periods of early and late glaciation bracketed a ∼2 Myr greenhouse interval-the Miocene Climatic Optimum (MCO). Floras, faunas, ice sheets, precipitation, pCO 2 , and ocean and atmospheric circulation mostly (but not ubiquitously) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
179
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(229 citation statements)
references
References 776 publications
(1,785 reference statements)
11
179
0
2
Order By: Relevance
“…The Miocene epoch encompasses much of the range of climate states between the Cenozoic endmembers of peak Eocene warmth and the modern ice-house state with extensive glaciation at both poles (Figure 1, Steinthorsdottir et al, 2020). Terrestrial and marine records show that Miocene climate BURLS ET AL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Miocene epoch encompasses much of the range of climate states between the Cenozoic endmembers of peak Eocene warmth and the modern ice-house state with extensive glaciation at both poles (Figure 1, Steinthorsdottir et al, 2020). Terrestrial and marine records show that Miocene climate BURLS ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Typical proxy estimates for the Miocene are in the 300-600 ppmv range (Figure 1, Foster et al, 2012Foster et al, , 2017Sosdian et al, 2018), although during the MCO, recent reconstructions suggest that CO 2 may have been as high as 800-1,100 ppm (Sosdian et al, 2018;Stoll et al, 2019). A full description of the Miocene CO 2 reconstructions and their uncertainties is given in Section 8 of (Steinthorsdottir et al, 2020). A prolonged carbon isotope excursion between ∼16.7 Ma and ∼13.5 Ma (the Monterey Excursion; Vincent & Berger, 1985) documents a marked perturbation of the carbon cycle at this time, modulated by orbital forcing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that Antarctic ice volume throughout the middle Miocene may have been much more variable than implied by the relatively low-resolution data of Modestou et al (2020). For example, it has been suggested that peak middle Miocene warmth was potentially associated with little ice on Antarctica (Miller et al, 2020;Stap et al, 2016; discussed in more detail in Steinthorsdottir et al, 2020). In addition, the Antarctic ice sheet response to pCO 2 depends strongly on multiple factors such as the dynamics of pCO 2 change, orbital parameters, and precipitation lapse rate (Stap et al, 2019).…”
Section: Deep Heat But Big Ice?mentioning
confidence: 99%
“…The Miocene climatic optimum (MCO, ∼16.5–15 Ma) is the most recent interval with atmospheric CO 2 substantially elevated above that of the early 21 st century, with boron isotope and alkenone δ 13 C‐derived estimates (Sosdian et al., 2018; Super et al., 2018) constraining peak CO 2 to around 400–800 ppm, declining to 200–400 ppm after the Miocene climate transition (MCT, ∼14.5–13 Ma). The atmospheric CO 2 concentration of the MCO gave rise to a profoundly different world to today, with global mean surface temperature ∼3–6°C higher than preindustrial times (Hansen et al., 2013; Tierney et al., 2020) and a substantially reduced latitudinal temperature gradient (Goldner et al., 2014); also see the review paper in this issue for a more comprehensive summary of the climate and biota of the Miocene (Steinthorsdottir et al., 2020).…”
Section: Introductionmentioning
confidence: 99%